Multi-Modality Ayurveda Regime in the Management of Childhood Vitiligo w.s.r.to Shwitra: A Case Report. (AYUSHDHARA, 2023)
Patients of vitiligo are hated and neglected lot in the society. Great researches in the world have done lot of studies and experiments but no medicine has proved satisfactory in total eradication of the disease. Objective: To see the effect of multi-modality Ayurveda regime in the management of Childhood vitiligo/Shwitra. Methodology: Female patient 07yrs old had been experiencing symptoms of white Patches around the b/l eye and elbow since 5months. Ayurvedic medicines were used in the study for one year and six months. Discussion: The major goal of the multi-modality regime is to help to eliminate white patches. Bakuchi Ghanvati, Mahamanjishtadi kadha, Panchtikta ghruta guggul, Krumikuthar rasa were given orally. Bakuchi tail for local application and daily Hanuman chalisa path advised to patient. This treatment for one half year continued which showed excellent result in the patient. Conclusion: The effect of Dravya and Adravya shaman chikitsa has shown encouraging results in the repigmentation of the affected skin. Not many complications were observed in the patients at the end of the study. Ayurveda has distinctive concepts with all disease called as Chikitsa siddhanta, which work and stand for a long period of time. Since the therapy for Vitiligo has limitation in other pathies, Ayurvedic management of vitiligo is one of the most effective therapy and which have less chances of recurrence.